Thrombi Formed in a Chandler Loop Mimic Human Arterial Thrombi in Structure and PAI-1 Content and Distribution - Robbie, Linda A; Young, Simon P; Bennett, Bruce; Booth, Nuala A (Thrombosis and Haemostasis, 1997)
We have previously shown that whole blood clots prepared under static conditions are a poor model for human thrombi formed in vivo. The most striking contrast is in the PAI-1 content, some 100 times lower in static clots than in human thrombi. This study aimed to evaluate thrombi formed in an artificial circulation (Chandler loop) using whole blood augmented with platelets. Citrated blood was recalcified and placed in tubing, which was sealed to form a closed loop and circulated. Immunohistochemical staining revealed morphology very similar to human thrombi formed in vivo, comprising dense platelet-rich heads and fibrin-rich tails. Strong positive staining for PAI-1 was observed in fibrin-rich areas of both the head and the tail. The PAI-1 content of the thrombi increased significantly on augmentation of blood with isolated platelets, and reached levels comparable with those in human thrombi. These Chandler thrombi thus provide an appropriate model system for the study of thrombus lysis, in contrast to static blood clots.